Poverty in Israel - Dirk Michel; Claudia Schertges (Social Work & Society, 2007)
The paper deals with poverty within Israel. Against the background of the history of pre-state Israel and the developments after the establishment of the State of Israel in 1948 the historical roots of Israeli poverty are analyzed. Thus the 'socialist'-Zionist project, ethnic exclusion, religious and intra-Jewish ethnic lines of conflict as well as the Bedouins, Druzes and Israeli Arabs as 'specific' Israeli citizen are discussed. Despite the economic growth in Israel since 2003 'the majority of Israeli wage earners (over 60percent) earned less than $1,450 a month last year' (Goldstein 2007, p. 1). In 2004 1.3 million Israelis lived below the poverty line, a number which in 2005 increased to more than 1.5 million Israelis. In spite of growing economic prosperity the proportion of families belonging to the working-poor, i.e. families with at least one family member in paid employment, increased from 11.4 percent in 2004 to 12.2 percent in 2005. The percentage of poor families in the working population increased from 40.6 percent to 43.1 percent. Nearly 60 percent of the 'working-poor' were working fulltime (Sinai 2006a, Shaoul 2006). 42 percent of Israeli Arab families are living below the poverty line. The average wages are less than half the wages of Ashkenazi Jews. Every second Israeli Arab child lives in poverty. When in 1996 to 2001 the unemployment rate of the Jewish Israelis increased by about 53 percent, the unemployment rate of the Arab Israelis increased by 126 percent (cf. Shaoul 2006). 80 percent of Israelis regard themselves as poor. 23 percent of the pensioners are living below the poverty line. Poverty among children increased in 1988 to 2005 by about 50 percent. Approximately one fifth of all under-age children (714.000) in Israel are suffering from hunger (cf. Shaoul 2006). 75 percent of the poor families cannot afford medicine and 70 percent are dependant on food donations (cf. Sinai 2005b). Nearly one third of the Holocaust survivors are living in poverty. Some of the Holocaust survivors get $ 600,- per month from the German government, whilst other Holocaust survivors receive only $ 350,- per month from the Israeli Ministry of Finance and the Holocaust survivors that immigrated to Israel after 1953 (who amount to 70 percent of the Holocaust survivors in Israel) only receive the general national pension. Nearly 20 percent of the Holocaust survivors are at the present time 86 years and older, 70 percent are older than 76 years. (cf. Medina 2007, p. 1) They are not entitled to a supplementary payment or to compensation. But the problematic economic situation of the Holocaust survivors is neither new information nor an unknown fact. As a result of the precarious situation several are in need of the help of welfare organizations, because they cannot afford to some degree their necessary medicine.